The Genetics of the Pig (2nd Edition) - Rothschild, Max F (CABI, 2014)
The first edition of The Genetics of the Pig was published more than 12 years ago. During the past several years a deep transformation has occurred in all of the biological sciences. Beginning in 2001, several mammalian genomes were sequenced. The latest addition to this list is the pig genome, whose first draft sequence was obtained at the end of 2009. While the annotation of the pig genome is still an ongoing process one can confidently expect that in the near future this process will be significantly advanced. These developments in the biological sciences have led to the practical implementation of powerful laboratory methods which, together with the emer- gence of advanced bioinformatics, have caused dramatic accumulations of new data in diverse databases. Genetic theory and practice have also evolved considerably over the last 12 years. The previ- ously separate fields of classical and quantitative genetics have now been joined with genomics, molecular genetics and immunogenetics, creating new methods and insights into understanding numerous biological processes. Today, more than in the past, genetics serves as a key pillar of modern agricultural sciences, medicine and the biotechnological industry. Animal breeders and geneticists, more widely than ever before, are using knowledge from the different fields of genet- ics for development and improvement of their livestock. Given these dramatic changes in current genetic applications and theory it seems an appropriate time to publish the second edition of books devoted to genetics of domestic livestock species. The Genetics of the Pig opens this series of books.